Fabrication of composite materials by using short pineapple leaf fiber PALF : A Review - Mr. P. C. Dagade; Prof. S. M. Shaikh (International Journal of Innovations in Engineering Research and Technology, 2021)
Composite materials (also called composition materials or shortened to composites) are materials made from two or more constituent materials with significantly different physical or chemical properties, that when combined, produce a material with characteristics different from the individual components. The individual components remain separate and distinct within the finished structure. The new material may be preferred for many reasons: common examples include materials which are stronger, lighter or less expensive when compared to traditional materials. In the last decades, the use of natural fibers as reinforcement in polymeric composites for technical application has been a research subject of scientist. Interest in natural fibers has increased worldwide due to their low cost, low density, hardness, higher fatigue endurance, good thermal and mechanical resistivity and to their environmental friendliness.